A combination of heterogeneous catalysis and photocatalysis for the olefination of quinoxalin-2(1H)-ones with ketones in water: a green and efficient route to (Z)-enaminones. Issue 5 (25th February 2021) - Xu, Jun; Huang, Lin; He, Lei; Ni, Zhigang; Shen, Jiabin; Li, Xiaoling; Chen, Kaixian; Li, Wanmei; Zhang, Pengfei
Abstract : This study describes a novel aqueous reaction for the synthesis of ( Z )-enaminones through a combination of heterogeneous catalysis and photocatalysis. Abstract : Herein, a novel aqueous reaction for the olefination of quinoxalin-2(1 H )-ones with ketones through a combinational strategy is described. This reaction features very mild conditions using a simple and cheap catalyst for the synthesis of ( Z )-enaminones with moderate-to-good yields. Such a methodology successfully combines the heterogeneous Mannich reaction with photocatalysis, and provides a green and practical approach for the synthesis of potentially bioactive ( Z )-enaminones with a 3, 4-dihydroquinoxalin-2(1 H )-one skeleton.